Bioanalytical and chemical-specific screening of contaminants of concern in three California (USA) watersheds. Issue 5 (May 2022) - Maruya, Keith A.; Lao, Wenjian; Vandervort, Darcy R.; Fadness, Richard; Lyons, Michael; Mehinto, Alvine C.
Abstract: To broaden the scope of contaminants monitored in human-impacted riverine systems, water, sediment, and treated wastewater effluent were analyzed using receptor-based cell assays that provide an integrated response to chemicals based on their mode of biological activity. Samples were collected from three California (USA) watersheds with varying degrees of urbanization and discharge from municipal wastewater treatment plants (WWTPs). To complement cell assay results, samples were also analyzed for a suite of contaminants of emerging concern (CECs) using gas and liquid chromatography-mass spectrometry (GC- and LC-MS/MS). For most water and sediment samples, bioassay equivalent concentrations for estrogen and glucocorticoid receptor assays (ER- and GR-BEQs, respectively) were near or below reporting limits. Measured CEC concentrations compared to monitoring trigger values established by a science advisory panel indicated minimal to moderate concern in water but suggested that select pesticides (pyrethroids and fipronil) had accumulated to levels of greater concern in river sediments. Integrating robust, standardized bioanalytical tools such as the ER and GR assays utilized in this study into existing chemical-specific monitoring and assessment efforts will enhance future CEC monitoring efforts in impacted riverine systems and coastal watersheds. Abstract : Bioanalytical screening; Water quality; Estrogen receptor; Glucocorticoid receptor; Contaminants of emerging concern (CECs); Aquatic ecosystems.